Behavior Related to the Success of Pulmonary TB Treatment - Mohammad Fauzi; Edy Soesanto; Ratih Sari Wardani; Mohammad Fatkhul Mubin; Aric Vranada (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pulmonary Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis, this disease becomes a public health problem, especially if there is a break in treatment which has an impact on TB drug resistance. The purpose of this study is to see the correlation or relationship of determinant factors that influence the success of pulmonary tuberculosis treatment. The type of research is Observational Analytical with a Cross Sectional approach. Data collection uses questionnaires, observations and interviews. The population is 158 and the sample is 91 respondents with cluster sampling. The study was conducted in Parigi Moutong Regency during February-June 2025. Of the 91 respondents who were 94.5% compliant with taking medication, 75.8% had good Family Support, 75.8% had Drug Supervisor (PMO) Support and 83.5% had Health Worker Support, the results of the chi square test showed a relationship between medication adherence and the success of Pulmonary TB Treatment p = 0.000 <0.05, there was a relationship between family support and the success of Pulmonary TB Treatment p = 0.001 <0.05, there was a relationship between support (PMO) and the success of Pulmonary TB Treatment p = 0.001 <0.05 and there was a relationship between Health Worker support and the success of Pulmonary TB Treatment p = 0.000 <0.005. Conclusion There is a relationship between behavior (medication adherence, family support, PMO support and health worker support) and the success of pulmonary TB treatment.